Beneath the tamarind tree. a story of courage, family, and the lost schoolgirls of Boko Haram - Sesay, Isha. (New York, NY : Dey St. an imprint of William Morrow, 2019)
In Beneath the Tamarind Tree, having developed unprecedented access to the Chibok girls, Sesay shares an intimate account of the night Boko Haram attacked, exclusive details about their years in captivity, and their daring tales of escape. We meet Priscilla, who dreamed of becoming a doctor, Saa, who juggled schoolwork with family obligations, Mary, who fought constant homesickness to stay in school, and Dorcas, who planned to be the first in her family to get a college degree.
Includes bibliographical references and index.
Keywords: Boko Haram